Effort Increase Competence Teacher Through Teaching Practices at SDN 050662 Peace State - Ikramullah, Fiza; Yasyarah, Syabilla; Desfika, Tria (Journal of General Education Science, 2023)
Increasing teacher competence is an important factor in improving the process of teaching and learning activities so as to create quality education. Therefore that, teacher must capableknow whatpeaceelementaryschoolstudentsneedstableinprocessStudyteachso that creation environment Which safe and inclusive. One effort to encourage student motivation in learning is by look for practical Study Which interesting so that creation that interaction Good between teachers And student in process learning to teach inside class.Method study used is approach qualitative, that is involve ideas practical Teacher in teaching in Engineering class study Which we use For gather something research data in the form of literature reviews, observations and interviews. The results of interviews that we can carry out at the stable peace elementary school in activities to increase teacher competencethroughpracticalteachingsothattheycanmotivatestudentsinStudy teachso that can increase interest student in Study class if a Teacher have innovation in implement practical teach inside class so that good interaction between teachers and students is created in the teaching and learning process in the classroom. The aim of the research we conducted in elementary schools peace stable the goal so that increase quality Education Which quality and creating a safe and inclusive educational environment at SDN 050662 Stabat Peace.